Effects of cocaine on cell excitability - Eyzaguirre, Carlos (1951)
One is as old as the discovery of the Americas, empirical observation refers to the custom of the Andean Indians chew coca leaves (Erythroxilon coca) in order to prevent hunger and avoid fatigue. It is difficult to consider this interesting fact from an experimental point of view, since the physiological mechanisms related to the phenomena of hunger and fatigue are complicated. Cocaine, the active ingredient of coca leaves (Gardekem 1855), is probably the substance responsible for the effects noted.